AN ANALYSIS OF TEACHERS INSTRUCTIONAL TIME MANAGEMENT IN ENGLISH CLASSROOMS - Kuswandi, Dara Rizki (2016)
Starting 2013, the curriculum of Indonesia school system has changed from KTSP to curriculum 2013. Consequently, several elements of the curriculum were also changed, such as Standar Kompetensi Lulusan (graduate standard of competence), Standar Isi (standard of content), Standar Proses (standard of process), and Standar Penilaian (standard of assessment). The alteration of the standard of process in the new curriculum has an impact on the amount of time of the instructional session, particularly English class of the tenth grade. To provide portrayals of how to manage the instructional time and motivate teachers to increase their awareness towards the importance of the teacher instructional time management, the present study was organized to investigate two issues. The first issue was how the respondent teacher managed his instructional time. The second issue was the teacher's challenges in managing the instructional time in his English classes. This study employed a descriptive analysis method by using non-participant observation, open-ended interview, and written documents in the form of observation field notes, observation checklist sheets, and the teacher's lesson plans. The findings of the study show that most of the sessions were categorized effective but some were less effective. It also found several factors that challenge the effectiveness of the teacher's instructional time management such as interruptions from teacher and visitors, unexpected power outage, and student's behavior issues. Hence, the teacher should find the best strategy to manage the instructional time and overcome the challenges.;--- Pada tahun 2013, kurikulum pada sistem pendidikan Indonesia diubah dari KTSP menjadi Kurikulum 2013. Hal ini menyebabkan terjadinya perubahan pada Standar Kompetensi Lulusan, Standar Isi, Standar Proses, and Standar Penilaian. Perubahan dalam Standar Proses pada kurikulum baru mempengaruhi jumlah waktu instruksional guru, khususnya mata pelajaran bahasa Inggris di kelas X. Penelitian ini dilakukan untuk meneliti dua hal, yaitu cara responden mengelola waktu instruksionalnya dan tantangan yang dihadapi dalam mengelola waktu instruksional. Penelitian ini bertujuan untuk memberikan gambaran bagaimana cara mengelola waktu instruksional dan memotivasi guru untuk meningkatkan kesadaran akan penntingnya pengelolaan waktu instruksional. Penelitian ini dilaksanakan dengan metode deskriptif analisis dengan menggunakan pengamatan, waancara, dan dokumen tertulis dalam bentuk catatan pengamatan, lembar daftar mengamatan, dan Rencana Pelaksanaan Pembelajaran guru sebagai instrumen untuk memperoleh data. Temuan penelitian mennunjukan bahwa ekgiatan belajar mengajar yang dilaksanakan oleh responden cenderung efektif walaupun terdapat beberapa pertemuan yang kurang efektif. Selain itu, terdapat beberapa tantangan yang dihadapi responden dalam mengelola waktu instruksionalnya seperti gangguan dari guru tersebut atau tamu yang berkunjung ke dalam kelas, terhentinya aliran listrik secara tiba-tiba ketika menggunakan media elektronik, dan masalah perilaku siswa. Oleh karena itu, guru sebaiknya menemukan dan menggunakan strategi terbaik yang sesuai untuk mengelola waktu instruksional dan mengatasi tantangan yang dihadapi.